Med procesom 2016/17: Pregledna razstava Oddelka za arhitekturo, FGPA UM - Rozman Cafuta, Melita; Skalicky, Vanja; Šprah, Nataša (2017)
During the Process 2017/17 : Overview Exhibition of the Department of Architecture, FGPA UM. Med procesom 2016/17 (During the Process 2016/17) is the third consecutive publication of student project papers at the Department of Architecture at the Faculty of Civil Engineering, Transportation Engineering and Architecture of the University of Maribor. The publication informs the general public of the achieved study results, and is an excellent opportunity for us to analyse, and talk about, the results, the content and the connection between knowledge from project and theoretical subjects, and compulsory and elective subjects. In the publication, the subject description is followed by the description of the project paper, which, in most subjects, changes each year, and a graphic presentation. A wide range of topics students, teaching staff and other employees discuss during studies reflects the attitude of school to the perception of social development needs: from abstract and generally set project papers in junior years to project papers related to the research of contemporary topics or the search for solutions in the local environment in senior years.
Keywords: Department of Architecture; Faculty of Civil Engineering; Transportation Engineering and Architecture; University of Maribor; student project catalogue; academic year 2016/17